Second-look TURBT: evaluation of anatomopatological and oncologic results in a single center - Maltagliati, Matteo; Varca, Virginia; Milandri, Riccardo; Micali, Salvatore; Bocchialini, Tommaso; Rocco, Bernardo Maria Cesare; Gregori, Andrea (Acta Biomedica Atenei Parmensis, 2020)
Introduction: T1 bladder cancer is associated with a high risk of recurrence and progression; concomitant carcinoma in situ and/or multifocality are negative prognostic factors. Persistent disease after resection of T1 tumours has been observed in 33-55% of patients, and after resection of High-grade (HG) Ta tumour in 41,4%. It has been demonstrated that a second TURB can increase recurrence-free survival and it can make a restaging of the cancer. Patients and methods: From January 2011 to December 2016, 87 patients with superficial bladder tumor (Ta-T1), undergoing TURB and routine repeat TURB (Re-TURB) 4-6 weeks after the initial resection, were included in the study. Re-TURB was applied to the scar of the first resection and other suspicious lesions in the bladder. After the second-look, we studied the follow-up of each patient. Results: Specimens obtained during the second TURBT showed no tumor in 47 (54,02%) patients; 40 (45,98%) patients had residual cancer: 34 of them had cancer of the same stage, 6 patients of pT1 had a lower stage, and 3 had a higher stage. 5 patient underwent radical cistectomy immediatly after re-TURBT. During the first year of follow up, 15 patients had a recurrent bladder cancer; 2 of them underwent radical cistectomy. Conclusions: T1 bladder cancer is an high risk tumor, so that second-look TURBT is a valuable procedure for accurate staging of nonmuscle-invasive bladder cancer and it can guarantee a better eradication of the neoplasm.